Analisis Faktor Pola Makan Pada Balita Stunting: Transcultural Nursing: Analisis Faktor Pola Makan pada Balita Stunting dengan Pendekatan Transcultural Nursing - Maulina, Rifzul; Retnaningsih, Reny; Safitri, Rani; Amalia, Waifti (Amerta Nutrition, 2024)
Background: In 2022, prevalence of stunting in Indonesia reach 21.6%. The direct causes of stunting was nutritional intake. The problem of nutritional intake was related to the cultural practices of Indonesian, so this research used a transcultural nursing. Objectives: This study aimed to identify factors influencing feeding patterns in stunting children based on transcultural nursing. Methods: Cluster sampling was used for this cross-sectional with 145 mother-child pairs. The independent variables were maternal education, economics, regulations and policies, cultural values and lifestyle, social and family support, religiosity and philosophy and technology. The dependent variable was feeding pattern. The instrument used was a questionnaire. Spearman Rho (p-value=0.05) was used to analyze the relationship between variables. Results: Economic factors (p=0.031; r=0.250), government policies and norms (p=0.034; r=0.180), cultural and lifestyle values (p=0.001; r=0.540), social support and family (p=0.000; r=0.270), religious and philosophical beliefs (p=0.000; r=0.321), and technological developments (p=0.002; r=0.210) were associated with feeding pattern, no correlation between feeding pattern and mother's education (p=0.689). Conclusions: Economy, regulation and policy, cultural value and lifestyle, religiosity and philosophy, social support and family, and technology associated stunting child's feeding pattern. Cultural beliefs and lifestyle were the most important factors for stunting children's feeding patterns so it is envisaged that paramedics continue to expand their preventive and persuasive efforts by providing health consultations to moms and families.